ANALISIS EFEKTIVITAS PERKULIAHAN DARING MAHASISWA FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS KATOLIK SANTO THOMAS - Rumiris Lumban Gaol; Dewi Anzelina (Universitas Negeri Medan, 2022)
The purpose of this study was to analyze the effectiveness of student lectures at the fakultas keguruan dan ilmu pendidikan Universitas Katolik Santo Thomas. Components that refer to the implementation of courageous learning, factors and barriers to lectures, the value of character education and the benefits of lectures. This research is a quantitative descriptive study using a survey method conducted online. Data was obtained through filling out all questionnaires and answering questions distributed to respondents in the form of a google form. Based on the data analysis, the conclusions obtained from this research are 1. Lectures dare to be effectively used in the implementation of learning. 2. Lectures dare to be effective in the application of character education values, namely discipline, honesty, independence and responsibility.3. Online lectures are effective in applying the value of character education, namely hard work. 4. Online lectures are less effective in terms of obstacles and inhibiting factors for online lectures.5. Bold lessons are less effective in terms of the benefits of brave learning in the learning process.